UNLOCKING PRIVATE INVESTMENT BY EXPANDING THE SCOPE OF EXISTING TOLL ROAD PPPs AGREEMENTS - Azka, Fahmi Amika; Hendranastiti, Nur Dhani (Universitas Multimedia Nusantara, 2023)
Abstract - The inability of governments in many developing countries to provide basic infrastructure has encouraged the adoption of Public Private Partnership (PPP) schemes. However, many developing countries fail to attract sufficient private investment from the PPP market. This paper develops alternative schemes that can minimize the funding gap and promote sustainable infrastructure investment through modified PPP agreements at later stages of the project life cycle by making special tariff adjustments on existing toll roads. To answer research questions, both conceptual model development and empirical analysis are utilized. The study collects both quantitative and qualitative data for analysis and interpretatio. The results indicate that expanding the scope of existing PPP agreements increases the net present value as it allows for larger cash inflows at the start, leading to a faster payback period. Additionally, this scheme reduces the need for cash deficiency support during the initial period of operation. The alternative schemes encourage lower support for government subsidies, offer a reasonable tariff for users, and provide an attractive investment return for private interests. Keywords: Public Private Partnership; Concession Agreement; Toll Road; Sustainable Investment, Funding Gap